1994
DOI: 10.1093/jn/124.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Postabsorptive Metabolism of Nicotinic Acid in Rat Small Intestine May Affect Transport by Metabolic Trapping

Abstract: Postabsorptive metabolism of [3H]nicotinic acid by rat proximal jejunum was studied in vitro using the everted sac technique and in vivo by applying ligated loops. Metabolites were analyzed by HPLC with radiochemical detection. Within 60 min of incubation nicotinic acid was almost completely metabolized in vivo. Only 3.2% of the label could be detected in the original substrate nicotinic acid, whereas > 90% of the radioactivity present in the gut wall was nicotinamide. Further in vitro experiments revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…New research in human subjects suggests that the mechanism for NA absorptions in physiological amounts is dependent on an acidic pH and a specialised Na + -independent carrier-mediated system ( 33 ) . In higher concentrations, diffusion was observed to be the main mechanism in rats ( 34 ) . For NAM, absorption was suggested to occur via diffusion at twice the rate of NA ( 35 ) , but new research on NAM absorption is not available.…”
Section: Duodenummentioning
confidence: 99%
See 2 more Smart Citations
“…New research in human subjects suggests that the mechanism for NA absorptions in physiological amounts is dependent on an acidic pH and a specialised Na + -independent carrier-mediated system ( 33 ) . In higher concentrations, diffusion was observed to be the main mechanism in rats ( 34 ) . For NAM, absorption was suggested to occur via diffusion at twice the rate of NA ( 35 ) , but new research on NAM absorption is not available.…”
Section: Duodenummentioning
confidence: 99%
“…This was not expected, since the NAM-supplemented group had the highest duodenal values of niacin; at this point it is not explainable why this should result in the lowest niacin content of plasma. For rats, it was demonstrated that NAM is also able to pass from the bloodstream back to the lumen ( 34 ) . This could explain the previously mentioned results in the NAM group ( 12 ) , should it occur in ruminants as well.…”
Section: Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using various rat tissue preparations (Gross & Henderson, 1983) have led to the following possible pathway of NAD (or NADP) degradation to nicotinamide ( Fig. Data obtained from this and other reports (Elbert et al, 1986;Stein et al, 1994) have led to the general conclusion that cellular uptake of nicotinamide and nicotinic acid occurs primarily by simple diffusion. The initial step is an attack at the phosphodiester bond of NAD to form nicotinamide mononucleotide and adenosine monophosphate (AMP).…”
Section: Digestion and Absorption Of Dietary Niacinmentioning
confidence: 81%
“…Under different osmotic pressures, several factors may simultaneously influence the absorption of VBs. Firstly, the uptake of most VBs was shown to be a specific carrier‐mediated transport system at low concentration combined with a simple diffusion at high concentration (Casirola, Ferrari, Gastaldi, Patrini, & Rindi, ; Dakshinamurti, Chauhan, & Ebrahim, ; Daniel, Wille, & Rehner, ; Feder, Daniel, & Rehner, ; Middleton, ; Merrill, Edmondson, & McCormick, ; Said, Hollander, & Duong, ; Stein & Diamond, ; Stein et al, ). Low concentration of sodium will lead to a fall in uptake (Casirola et al, ).…”
Section: Resultsmentioning
confidence: 99%